Al-Shahadah fi al-Qur'an wa-al-Sunnah - Sharifah Bt Che Soh (Universiti Sains Islam Malaysia, 2014)
A research that has been conducted by the writer entitled "Concept of Witnesses in Al-Quran and Sunnah". In effort to accomplish this research, the main method used was a library literature by gathering information from the primary sources. At the same time. the writer also surfing on the Internet in order to gain extra-related information. The purpose of this research discuss about witnesses in Islamic Law. Many aspects have been discussed in detail about it. Firstly on the definition, Hukm of witnesses, condition of witnesses. the Hikmah from many sources and the condition of witness to show how systematically of the Islamic Law. In order to tell the verses of Al-Quran and Sunnah and ikhtilaf of Muslim scholar about the witness. On the discussing is based on the view and opinion of Muslim scholar about the situation of witnesses. In last chapter, discuss about the witness, types of witnesses like the entitlement of Allah, witnesses of the human, witnesses of the woman, the witnesses of the non-Muslim and the false of witnesses.